Immune response in peripheral axons delays disease progression in SOD1G93A mice. Issue 1 (December 2016) - Nardo, Giovanni; Trolese, Maria; de Vito, Giuseppe; Cecchi, Roberta; Riva, Nilo; Dina, Giorgia; Heath, Paul; Quattrini, Angelo; Shaw, Pamela; Piazza, Vincenzo; Bendotti, Caterina
Abstract Background Increasing evidence suggests that the immune system has a beneficial role in the progression of amyotrophic lateral sclerosis (ALS) although the mechanism remains unclear. Recently, we demonstrated that motor neurons (MNs) of C57SOD1G93A mice with slow disease progression activate molecules classically involved in the cross-talk with the immune system. This happens a lot less in 129SvSOD1G93A mice which, while expressing the same amount of transgene, had faster disease progression and earlier axonal damage. The present study investigated whether and how the immune response is involved in the preservation of motor axons in the mouse model of familial ALS with a more benign disease course. Methods First, the extent of axonal damage, Schwann cell proliferation, and neuromuscular junction (NMJ) denervation were compared between the two ALS mouse models at the disease onset. Then, we compared the expression levels of different immune molecules, the morphology of myelin sheaths, and the presence of blood-derived immune cell infiltrates in the sciatic nerve of the two SOD1G93A mouse strains using immunohistochemical, immunoblot, quantitative reverse transcription PCR, and rotating-polarization Coherent Anti-Stokes Raman Scattering techniques. Results Muscle denervation, axonal dysregulation, and myelin disruption together with reduced Schwann cell proliferation are prominent in 129SvSOD1G93A compared to C57SOD1G93A mice at the disease onset, and this correlates with a faster disease progression in the first strain. On the contrary, a striking increase of immune molecules such as CCL2, MHCI, and C3 was seen in sciatic nerves of slow progressor C57SOD1G93A mice and this was accompanied by heavy infiltration of CD8+ T lymphocytes and macrophages. These phenomena were not detectable in the peripheral nervous system of fast-progressing mice. Conclusions These data show for the first time that damaged MNs in SOD1-related ALS actively recruit immune cells in the peripheral nervous system to delay muscle denervation and prolong the lifespan. On the contrary, the lack of this response has a negative impact on the disease course.